Non-Tuareg Berber and the Genesis of Nomadic Northern Songhay - (:unkn) unknown (My University, 2015)
With massive borrowing resulting in systematic suppletion, the nomadic Northern Songhay languages, Tadaksahak and Tagdal, are some of the most striking products of intense language contact in Africa. While the importance of Berber in their formation is obvious, published comparisons have focused almost exclusively on Tuareg, the currently dominant Berber language of the region. This paper, however, demonstrates that Tuareg-Songhay contact alone cannot adequately account for their emergence. Tadaksahak at least seems to have as its substrate not Tuareg, but rather a Western Berber language closely related to Tetserrét, a small minority language of Niger; such a language also played a role in the development of Tagdal. Western Berber influence, however, is not reconstructible at the proto-Northern-Songhay level, despite being attested in most Northern Songhay languages individually. A closer look at the Western Berber stratum in Tadaksahak indicates that language shift there was accompanied by broader cultural changes, including a shift away from the regional norm of cross-cousin marriage towards the North African preference for patrilineal parallel cousin marriage. These linguistic and cultural changes may have been part of an effort to assert an identity as specialists in Islamic learning, following regional political shifts around the sixteenth century.
Keywords: African Research